A Framework for Prioritizing Nutrition-Sensitive Interventions: Beyond Outputs to Impact - Mizan, Arefin; Roy, Prantik; Hasan, A M Rumayan; Mahmood, Shehrin; Rasheed, Sabrina (WorldFish, 2024)
This policy brief proposes a comprehensive evaluation framework tailored to Bangladesh, designed to assess the broader impacts of nutrition-sensitive interventions (NSIs) beyond traditional outputs. This framework emphasizes multi-dimensional outcomes, such as the interplay between agricultural productivity, food security, and nutritional improvement. It also incorporates contextual sensitivity, stakeholder engagement, and sustainability as core components of the evaluation process. Drawing from successful applications in public health in Southeast Asia, it demonstrates the ability to capture the intricate pathways through which interventions influence long-term health and nutrition outcomes. By adopting this new approach, Bangladesh can significantly improve the effectiveness and scalability of its nutrition-sensitive interventions, ensuring that they not only meet immediate food security goals but also contribute to long-term improvements in public health and nutrition.